Sensorised hand-held gripper for assessment of kinematics and dynamics features in assembly tasks - Choo, Wei Jie (Nanyang Technological University, 2021)
A sensorised gripper tool which features force/torque sensing as well as motion tracking is developed. The tool is intended for kinematics and dynamics analysis of interaction forces during assembly tasks. In this thesis, we first cover the rapid prototyping process. The procedure to calibrate a six-axis F/T sensor is detailed. A simple implementation of extracting tool position and orientation from a motion capture system is shown. Experiments are conducted to show viability of the tool for its intended purpose.